Identifikasi Peranan Orang Tua Wirausaha Dalam Pembentukan Karakter Entrepreneurial Spirit Dan Keberlangsungan Business Project Mahasiswa Universitas Ciputra - Dewi M. Immanuel; Metta Padmalia (Jurnal Ekonomi dan Bisnis, 2016)
This study aims to know whether the character of the entrepreneurial spirit of Ciputra University students which is expected to be the factor in being a successful enterprenour in the future, is influenced by parent who has a career as an independent enterprenour.  The population of the study is students who have completed a minimum of two year study, have  a sustainable business project at the time being, and have parents as family business entrepreneur. This is an exploratory qualitative research done by conducting in-depth interviews to students who become informants. Results from this study indicated that the character of the entrepreneurial spirit in the students themselves can be formed through an educational process, and also through action and the way of thought from parents in running the business. Character of entrepreneurial spirit is professionally sharpened the students in learning process at Ciputra University which is based on entrepreneurship.